Compensating rest allowances: some findings and implications for management arising from recent research - Belbin, R. M. (College of Aeronautics, 1956)
In November 1953 a research project was started at the College of Aeronautics to study Work Study rating, rest and fatigue allowances. This project has been carried out under the sponsorship of the Department of Scientific and Industrial Research with counterpart funds made avail¬able through the Conditional Aid Scheme. At the commencement of this project it was agreed that our special concern would be rest allowances and that we would consider rating only in so far as it became a necessary part of our study of rest allowances. This report is not intended to present results covering the whole of our investigations. The work carried out by.J. A, C. Williams who was any colleague in research until April, 1956 has been presented in previous reports and these are referred to in our list of references. Mr Williams has been especially concerned with the problem of heat stress and with the determination of a rational basis for Compensating Rest Allowances in relation to known heat loads. While this report cannot be regarded therefore as comprehensive it is hoped that for the general reader it will, however, cover sufficiently wide ground to justify some of the general conclusions that are reached at the end of this paper.